Revitalizing Jawi Script Literacy through Traditional Islamic Education: A Case from Indonesia - Abdul Gafur; Zainal Berlian; Endang Rochmiatun (STAI Hubbulwathan Duri, 2025)
The Jawi script, a traditional Arabic-based script historically used in Southeast Asia, is a unique characteristic of written communication in Indonesian Islamic boarding schools and constitutes a valuable cultural heritage that requires preservation. This study investigates the management of Jawi script instruction—covering planning, organization, implementation, and evaluation—at the Nurul Islam Seribandung Islamic Boarding School. Employing a qualitative descriptive design with a phenomenological approach, data were collected through observations, interviews, and documentation. The analysis followed three stages: data reduction, data presentation, and conclusion drawing. The findings reveal several challenges in the current management of Jawi script learning. In terms of planning, the script is not taught as a standalone subject but is embedded within general Islamic lessons using Javanese script, resulting in a lack of structured curriculum. The organizational aspect shows some progress, with task delegation among staff members in place. However, the implementation stage lacks a formal lesson plan or standardized teaching materials specifically dedicated to Jawi script. The evaluation process is present but only conducted at the end of the semester, limiting continuous assessment and feedback opportunities. This study underscores the need for a more structured and systematic approach to Jawi script instruction to ensure its sustainability and effective transmission to future generations. Strengthening instructional planning and integrating Jawi as a distinct subject could enhance both learning outcomes and cultural preservation efforts.